2002
DOI: 10.1002/1521-3773(20021115)41:22<4233::aid-anie4233>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Enantioselective Receptor for N-Protected Glutamate and Anomalous Solvent-Dependent Binding Properties

Abstract: The development of enantioselective receptors continues to be a challenging endeavor for supramolecular chemists, and enantioselective recognition of biologically relevant molecules in competitive solvents is particularly demanding. [1] Although numerous receptors have been developed for dicarboxylic acids and dicarboxylates, [2] only a few enantioselective receptors for chiral dicarboxylic acids (in the neutral diprotonated form) have been described, [3] and very few examples of enantioselective receptors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 4 publications
1
17
0
2
Order By: Relevance
“…Thalidomide was introduced in 1960s as a sedative and hypnotic drug for pregnant women. 12,13 In this current study, chiral recognition by a molecular bis(acrylamido)pyridine-based chirally imprinted polymer and its formation by a self-assembled process have been investigated. The drug has a stereocenter and it is used as a racemate with both the (S)-(2)-and (R)-(1)-enantiomers possessing biological effects for multiple myeloma and related plasma cell disorders in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalidomide was introduced in 1960s as a sedative and hypnotic drug for pregnant women. 12,13 In this current study, chiral recognition by a molecular bis(acrylamido)pyridine-based chirally imprinted polymer and its formation by a self-assembled process have been investigated. The drug has a stereocenter and it is used as a racemate with both the (S)-(2)-and (R)-(1)-enantiomers possessing biological effects for multiple myeloma and related plasma cell disorders in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In that case it was achieved by the copolymerization of different multifunctional monomers using the method of simultaneous multiple interactions with the template. 12,13 In this current study, chiral recognition by a molecular bis(acrylamido)pyridine-based chirally imprinted polymer and its formation by a self-assembled process have been investigated. A prepolymerized MIP formulation and the macromers were used to generate an engineered binding site complementary with the structure of the (R)-thalidomide that provided self-organization of the macromolecular multicomponent, resulting in the enhanced interfacial regions and surface interactions of the resultant nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The continued interest in novel macrocyclic thiourea ligands stems from their applications in many areas of chemistry and biochemistry, including ion-selective electrodes and optodes, 2 their easy complexation of anions 3 and N-protected glutamate dianion, 4 and antimicrobial studies. 5 Our ongoing studies are concerned with the simple, convenient preparation of these macrocycles.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the synthesis of calix [4]crown-5-sulfonyl imidazolidinethione from calix [4]crown-5-monosulfonyldiamine and carbon disulfide by intramolecular cyclization at room temperature in water. 7 In our study of these N-sulfonyl macrocycles, we now report the synthesis of methylene-bridged cyclophane-thiones from trisulfonamide and activated bisdithiocarbamate salts by intermolecular cyclization at room temperature in water (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…16 In our previous work, we have shown that to achieve effective enantioselective sensing of chiral anions, the receptors need to posses a minimum of two stereogenic centres. 17 This has also been demonstrated by other researchers, such as Kilburn et al, 18 Tucker et al 19 and James et al…”
Section: Introductionmentioning
confidence: 99%